Hubungan Usia dengan Kejadian Penyakit Jantung Koroner pada Pasien Rawat Jalan di RSUD dr. Doris Sylvanus Provinsi Kalimantan Tengah: The Correlation of Age with Coronary Heart Disease Incidence in Outpatients at RSUD dr. Doris Sylvanus Central Kalimantan Province - Melyani Melyani; Lensi Natalia Tambunan; Eva Prilelli Baringbing (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Coronary heart disease was to cardiovascular disease caused by arteries entering by plaque or pollutants that collect on the walls of the coronary arteries. The death rate due to coronary heart disease in Indonesian reaches 1.25 million people. Based on the 2018 National Riskesdes Report, in Central Kalimantan, heart disease was 1.3% or 10,189 cases of heart disease. The purpose of this research was to find out the Correlation between age and the incidence of coronary heart disease in outpatients at RSUD dr. Doris Sylvanus, Central Kalimantan Province. The design of this research was used cross sectional with the type of sampling of Simple Random Sampling. The population was 9759 respondents and the sample was 99 respondents who perform outpatient treatment at RSUD dr. Doris Sylvanus. The data was obtained from secondary data from medical records, then the data was tabulated and analyzed using the chi square test. Based on the research result, it may be obtained p value = 0,02 that was a significant relation exists between the age of coronary heart disease in patients outpatient at RSUD dr. Doris Sylvanus of Central Kalimantan Province. Coronary heart disease develops as a person ages, where the older he gets, the more likely he was to suffer from coronary heart disease.